Blood and urine levels of Pb, Cd and Hg in the general population of the Czech Republic and proposed reference values - Batáriová, Andrea; Spěváčková, Věra; Beneš, Bohuslav; Čejchanová, Mája; Šmíd, Jiří; Černá, Milena (International journal of hygiene and environmental health, 2006)
The Human Biological Monitoring (HBM) project was launched in the Czech Republic in 1994 as a part of the nation-wide Environmental Health Monitoring System to assess the exposure of the Czech general population to a broad spectrum of environmental contaminants. Over the years 2001-2003, the concentrations of lead (Pb), cadmium (Cd), and mercury (Hg) were determined in whole blood of 1188 adults (blood donors) and 333 children and in urine of 657 adults and 619 children. In adults, the median blood lead (B-Pb) level was 33microg/l. Men had higher B-Pb levels than women (medians 37microg/l vs. 25microg/l). Significantly higher B-Pb levels were observed in smokers compared to non-smokers (36microg/l vs. 31microg/l). In children, no sex-dependent differences were observed (median 31microg/l). In total, the median blood Cd level (B-Cd) in adults was 0.5microg/l. Smokers showed a median B-Cd level about 3 times as high as non-smokers (1.3microg/l vs. 0.40microg/l). Neither sex- nor age-related differences were observed in B-Cd levels. In 65% of children, B-Cd levels were below the limit of detection (LOD). The overall median urinary cadmium level (U-Cd) in adults was 0.31microg/g creatinine. Significantly higher U-Cd levels were found in women (median 0.39microg/g creatinine) compared to men (0.29microg/g creatinine). No significant differences were found between smokers and non-smokers. In more than 50% of children, the U-Cd level was below the LOD (=0.2microg/l). The median blood mercury (B-Hg) level in adults was 0.89microg/l. Significant differences were found between smokers (0.80microg/l) and non-smokers (0.92microg/l), and between men and women (0.86microg/l vs. 0.94microg/l). The median B-Hg level in children was 0.42microg/l and no sex-related differences were observed. The median urinary mercury (U-Hg) levels were 0.63microg/g creatinine in adults and 0.37microg/g creatinine in children. Significantly higher U-Hg levels were obtained in women and non-smokers compared to men and smokers, respectively. The B-Pb, B-Hg, U-Cd, and U-Hg levels significantly correlated with age. The following reference values were recommended for the period 2001-2003: 80, 65 and 55microg/l for B-Pb and 3.1, 4.0 and 1.5microg/l for B-Hg in men, women and children, respectively; 1.1microg/l and 1.2microg/g creatinine for B-Cd and U-Cd, respectively, in adult non-smokers; 5.4 and 12.0microg/g creatinine for U-Hg in men and women, respectively, and 3.7 and 5.5microg/g creatinine for U-Hg in boys and girls, respectively. The previous reference values for B-Pb and B-Cd needed revision and were reduced.
Keywords: Cadmium; Female; lidé středního věku; Environmental Monitoring; Reference Values; Adolescent; kadmium; mužské pohlaví; Financing, Organized; dospělí; rtuť; Middle Aged; olovo; ženské pohlaví; Child; Mercury; Lead; financování organizované; referenční hodnoty; dítě; Adult; monitorování životního prostředí; Male; mladiství